PENYULUHAN PENGEMBANGAN PELAPORAN BUMDES UNTUK MENDUKUNG PENGAMBILAN KEPUTUSAN BERKELANJUTAN PADA KELOMPOK BUMDES YANG TERGABUNG DALAM ASOSIASI PEMERINTAH DESA SELURUH INDONESIA (APDESI) DI KECAMATAN WOLASI SULAWESI TENGGARA - Asni, Nur; Wawo, Andi Basru; Husin, Husin; Akib, Mulyati; Darmawati, Tuti; Nurdin, Emillia; Mirosea, Nitri; Lestari, Kurnia Cahya; Andini, Sarah; Aksa, Putriana (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
Sustainable village development (village SDGs) is a form of implementation and contribution of villages in achieving national SDGs. BUMDes, as a business entity in the village area, has a significant role in village SDGs. Community Service (PKM) activities focus on literacy in managing sustainable BUMDes businesses by orienting themselves towards profit aspects and considering the village's social and environmental aspects. Therefore, PKM aims to increase knowledge of sustainability reports as a source of information in BUMDes' strategic decision-making. Participants in this PKM activity involved village heads and BUMDes administrators in 6 (six) villages that are members of the Association of Indonesian Village Governments (APDESI) in Wolasi District, Southeast Sulawesi Province. Six villages were implemented, focusing on Wolasi District, South Konawe Regency, involving 20 BUMDes administrators. The PKM implementation method uses three approaches, namely active presentations, discussions, and exercises. The results of the PKM activity showed the participants' enthusiasm for actively participating in each activity session. The evaluation results also demonstrated increased participants' understanding of aspects of village sustainability in general and Village-Owned Enterprises (BUMDes) in particular, as well as the role of sustainability reports as a critical source of information in supporting sustainable decision-making. The results of the PKM activities are expected to serve as a reference for the sustainable development of BUMDes managers who are members of APDESI in Wolasi District.